Bulk metallic glass casting investigated using high-speed infrared monitoring and complementary fast scanning calorimetry. (1st June 2018) - Haag, Fabian; Geisel, Steffen; Kurtuldu, Güven; Löffler, Jörg F.
Abstract: This study describes a method which has been developed to monitor flow and cooling during casting using a high-speed infrared camera. The spatial and temporal resolutions were 60 μm and 1 ms, respectively. Calibration was performed to obtain the local, quantitative temperature history of a wedge-shaped specimen after post processing. Depending on microstructure (amorphous vs. crystalline) a temperature measurement accuracy of ±3 K or ±5 K was achieved. The temperature data recorded for a low-melting Au-based alloy during casting were compared thoroughly with its crystallization kinetics. The high-speed infrared measurements correlate well with fast differential scanning calorimetry (FDSC) results. This emphasizes the great potential of both techniques for studying fundamental processes which occur during casting. Graphical abstract: Image 1